(untitled) (Annals of Bangladesh Agriculture, 2021)
A native Trichoderma isolate was collected from the agricultural soil of Gazipur. This isolate was identified as a Trichoderma asperellum through morphology and analysis of internal transcribed spacer (ITS) region of ribosomal RNA gene sequence and reconstruction of the phylogenetic tree. The antagonistic effects of the newly identified T. asperellum isolate were assessed against brinjal bacterial wilt caused by Ralstonia solanacearum both in vitro and in planta. Both qualitative and quantitative bioassays were conducted in vitro. For qualitative tests, dual culture and antibacterial activity were carried out, and pathogen growth was observed visually. The antagonism of T. asperellum cell free culture filtrate on the growth of R. solanacearum was conducted in a quantitative test. Successful antagonism was recorded after both in vitro qualitative tests. In addition, the lowest colony forming unit was recorded in 100% of CFC (2.4±0.51 ×103 cfu/ml) in quantitative test. The T. asperellum inoculated plant showed low disease incidence (13.33%) when seedlings were challenged with R. solanacearum in planta experiment. Disease incidence was 100% for seedlings when treated with only R. solanacearum. The results showed that the isolated and identified T. asperellum isolate suppressed R. solanacearum growth in vitro and protected the seedling from wilting in planta. Therefore, this isolate could be considered as a potential isolate. Ann. Bangladesh Agric. (2020) 24(2) : 107-120